The influencing factors and pathways of China’s green finance development towards the Carbon Peaking and Carbon Neutrality —evidence from fuzzy-set qualitative comparative analysis based on 30 provinces of China - Wang, Hong-sheng; Lee, Jin-man; Hao, Zheng (Frontiers in Environmental Science, 2023)
The development of green finance is an important support for the realization of China's carbon peaking and carbon neutrality goals. However, the factors behind green finance are not clear，it is an inevitable requirement to explore the influencing factors and paths of the development of green finance. Therefore, this study applies fuzzy-set qualitative comparative analysis (fsQCA) to the sample of provinces, autonomous regions and municipalities directly under the central government in China. Univariates such as economic development, industrial structure, government investment in environmental protection and green innovation capability are not necessary conditions for the development of green finance. We also demonstrate three pathways to high development of green finance, among which the conditions show relationships of complementarity and substitutability. To enhance the development of green finance in China, the government needs to increase environmental spending to drive change in the market and enhance regional green innovation capabilities.